Immune cell responses to amyloid-beta proteins: What is the extent and implications of amyloid-beta induced cytotoxicity in microglial cells and peripheral blood mononuclear cells? - Cao, A. (The Young Researcher, 2017)
Alzheimer’s disease (AD) is a neurodegenerative disease with cognitive and physical symptoms. Scientists generally accept the amyloid cascade hypothesis as the defining focus of AD pathology. Past studies have indicated that Aβ oligomers induced cytotoxicity in immune cells, but the role of Aβ monomers has remained largely unexplored. The purpose of this study is to confirm the cytotoxicity exhibited by Aβ oligomer and immune cell interactions, and to discover whether Aβ monomer interactions will produce a similar response. We used lyophilized Aβ peptides to generate monomers and oligomers, and then added them into cultured BV2 microglial cells and peripheral blood mononuclear cells (PBMCs). After incubation, we used a Glo-Assay procedure to measure Aβ induced cytotoxicity based on cell viability. Ultimately, it was found that Aβ oligomers were more prone to induce cytotoxicity than monomers. The results imply that PBMCs show a greater sensitivity to Aβ proteins than microglial cells.